Effect of pasteurization time and temperature on the physico-biochemical properties of soursop (Annona muricata L.) juice - Argo, Bambang Dwi; Islami, Reydita Claudy; Khoir, Nurul Hidayatul (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2024)
This study aimed to determine the effect of pasteurization time and temperature on soursop juice characteristics. Soursop (Anonna muricata L.), a climacteric fruit, is a high source of natural antioxidants and contains polyphenol oxidase (PPO) enzyme, which causes browning and can reduce the phenol content in fruit which can reduce antioxidant activity. The pasteurization process was carried out to inactivate PPO in soursop juice production. Soursop juice was prepared from soursop fruit pulp pasteurized at temperatures (56, 62, 68, 74, and 80 oC) for various pasteurization times (5, 10, and 15 minutes). Time and temperature of pasteurization had a significant effect (ρ < 0.05) on physical characteristics (Total Soluble Solid/TSS, viscosity, pH, and colour), polyphenol oxidase enzyme activity, antioxidant activity, and microbial population. Pasteurization at 62 ˚C for 5 minutes can maintain antioxidant activity with the greatest total phenol of 85.45 ± 3.5 mg GAE/100 g, total flavonoid of 71.38 ± 6.9 mg QE/100 g, and antioxidant activity of 76.91 ± 0, 33%. Pasteurization at 80 ˚C for 15 minutes can reduce the total number of bacteria from 350 ± 24 CFU/mL to 54 ± 22 CFU/mL, which has a TSS value of 13.73 ˚brix, viscosity of 928.67 mPa, pH of 4.40, a total colour change of 0.556, and has the lowest PPO enzyme specific activity of 0.0005 U/mg with enzyme inactivation of 93%.